2003
DOI: 10.1080/0028825x.2003.9512846
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator behaviour, not increased resources, boosts seed set on forest edges in a New Zealand Loranthaceous mistletoe

Abstract: these variables to proportion fruit set. In agreement with previous studies, unmanipulated plants were found to be strongly pollen limited, especially in shady locations. However, on plants receiving handpollination, fruit set was uniformly high and was unaffected by edge exposure or light levels. Direct observation of flower visitation rates by birds in the 2000/01 season showed that edge flowers were visited twice as often as interior flowers. These results show that the higher fruit set on edges is due to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…In New Zealand, strong pollen limitation has been found in populations of several bird-pollinated species Kelly et al 2000Kelly et al , 2004Montgomery et al 2001Montgomery et al ,2003Molloy 2004). Recent work has attempted to identify the ecological correlates of pollen limitation within and between populations in these species.…”
Section: Pollen and Seed Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand, strong pollen limitation has been found in populations of several bird-pollinated species Kelly et al 2000Kelly et al , 2004Montgomery et al 2001Montgomery et al ,2003Molloy 2004). Recent work has attempted to identify the ecological correlates of pollen limitation within and between populations in these species.…”
Section: Pollen and Seed Limitationmentioning
confidence: 99%
“…Hand-pollinations confirm that interior plants are limited by pollen supply and not by the resources needed to mature the fruit. Moreover, observations of the plants showed that visitation rates to plants by birds are greater on edge plants than in interior plants (Montgomery et al 2003). It appears, therefore, that these plants may be tolerant of some degree of forest fragmentation and take advantage of the increased edginess that it creates.…”
Section: Pollen and Seed Limitationmentioning
confidence: 99%
“…1A and B). Elaborate pollination and seed dispersal mechanisms involving birds have evolved in some of these loranth species (69,79,104,109,121,144,176). For example, birds pry open the fused corollas to reach their nectar reward, upon which the pollen "explodes" onto the bird's head (109,121).…”
Section: Mistletoe Biologymentioning
confidence: 99%
“…Unless buds are opened by animals, the flower has a very low probability of producing a seed. Consequently, P. tetrapetala fruit set is frequently pollen limited; this has been shown for Craigieburn for 1993(Robertson et al 1999Kelly et al 2004), but for only 2 years in the mid 1990s at Ohau (Robertson et al 1999;Montgomery et al 2003;Robertson et al 2005). Therefore, we quantified pollen limitation at Ohau and Craigieburn during the course of the seed-limitation experiment, as it is important to measure both at the same time (Ashman et al 2004).…”
Section: Pollen Limitationmentioning
confidence: 99%